2019
DOI: 10.3389/fpls.2019.00305
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Red:Blue LED Lights on Resource Use Efficiency and Nutritional Properties of Indoor Grown Sweet Basil

Abstract: Indoor plant cultivation can result in significantly improved resource use efficiency (surface, water, and nutrients) as compared to traditional growing systems, but illumination costs are still high. LEDs (light emitting diodes) are gaining attention for indoor cultivation because of their ability to provide light of different spectra. In the light spectrum, red and blue regions are often considered the major plants’ energy sources for photosynthetic CO2 assimilation. This study aims at identifying the role p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
172
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(214 citation statements)
references
References 74 publications
17
172
4
4
Order By: Relevance
“…Consistently, Zhang and Folta (2012) reported that as green light intensity increased, the amount of anthocyanin in arabidopsis decreased to half the level present in plants grown under combined R&B light. Also, Pennisi et al (2019) reported that substituting green light for red light significantly decreased antioxidant capacity and flavonoid concentration in basil plants. It was postulated that the decreased phytochemical concentration under green light treatments is caused by the coactions of decreased red and/or blue light proportions and an increasing reversal of blue light-induced effects by green light.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Zhang and Folta (2012) reported that as green light intensity increased, the amount of anthocyanin in arabidopsis decreased to half the level present in plants grown under combined R&B light. Also, Pennisi et al (2019) reported that substituting green light for red light significantly decreased antioxidant capacity and flavonoid concentration in basil plants. It was postulated that the decreased phytochemical concentration under green light treatments is caused by the coactions of decreased red and/or blue light proportions and an increasing reversal of blue light-induced effects by green light.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study sought to un-pick the influences of Red and Blue light on growth and photosynthetic efficiency in sweet basil and found that quantum efficiency in PSII was lower under Red/Blue LED light arrays when the Red portion of the light array was greater than double the Blue (2:1). This was reversed when light ratios were more equal (1:1) [57]. It is the presence of the Photosystem II Primary Donor protein P680 in PSII which absorbs maximum light energy at 680 nm (Red) and Photosystem I Primary Donor P700 in PSI which absorbs maximum light energy at 700 nm (Red) and these might be responsible for the effects on the stomatal conductance Gs [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…In the indoor plant cultivation of sweet basil (Ocimum basilicum cv. Superbo, Sais seeds, Cesena, Italy), Pennisi et al (2019) also reported that the greatest biomass production was achieved with the correct combination of RB-LED lightings, which resulted in highest Chl content, water and energy use efficiency [54] . The fact that red light supplemented with blue light which increased productivity is linked to enhanced photosynthetic performance has also been reported in many other plant species.…”
Section: Productivity Is Closely Linked To Both the Photosynthetic Pementioning
confidence: 97%
“…In addition to red light, many studies have manipulated the proportion of blue light necessary for normal plant growth [13,15,16,39,48] . Supplementing appropriate amount of blue light to red light results in dramatic effects on the morphology and anatomy structure [13,18,23,[48][49][50] , chloroplast structure [31,48,51,52] and photosynthetic performance [18,36,39,[53][54] .…”
Section: Productivity Is Closely Linked To Both the Photosynthetic Pementioning
confidence: 99%